The Epigenetic Faces of ULTRAPETALA1 - Ornelas-Ayala, Diego; Garay-Arroyo, Adriana; García-Ponce, Berenice; R. Álvarez-Buylla, Elena; Sanchez, María de la Paz (Frontiers in Plant Science, 2021)
The ULTRAPETALA1 (ULT1) is a versatile plant-exclusive protein described as a TrxG factor that regulates transcriptional activation and counteract PcG repressor function. As part of TrxG, ULT1 interacts with ATX1 to regulate H3K4me3 activation mark deposition. However, our recent studies indicate that ULT1 can also act independently of ATX1. Moreover, the ULT1 ability to interact with transcriptional factors and PcG proteins points out a versatile protein with other roles. Therefore, in this work we revised recent information about the Arabidopsis ULT1 function to understand the roles of ULT1 in plant development. Furthermore, we discuss the molecular mechanisms of ULT1, highlighting its epigenetic role, in which ULT1 seem to have characteristics of an epigenetic molecular switch that regulates repression and activation processes via TrxG and PcG complexes.